Verb Aspect in Persian and Bosnian Languages - Gačanin, Sabaheta (Prilozi za orijentalnu filologiju, 2017)
This paper is a contrastive analysis of the grammatical category of the verb aspect, as well as the analysis of general problems related to the verb aspect and aspectuality in Persian and Bosnian, through the semantic and grammatical analyses of the aspect forms in both languages. The verb aspect, although an independent grammatical category, in both languages must be examined within the broader category of aspectuality, since aspect, most frequently, is in interaction with aktionsart and verb tense. Contrastive analysis of the verb aspect category between the representatives of Slavonic and Indo-Iranian languages taken here is very desirable, since the majority of linguists believe that only in these languages there is a close correspondence between the aspect meanings and morphological tools used to express them.